Proposal of a Care Line for Meningococcemia: Detailing the model (Research, Society and Development, 2022)
Meningococcal disease is an infection caused by the bacterium Neisseria meningitidis, and is characterized by generating, among other symptoms, malaise, chills and headache. Data from recent years show a relative decrease in the number of cases of this disease in Brazil, however, this disease still remains a serious public health problem for the country. Therefore, the objective of this study was to propose the creation of a new Line of Care for meningococcemia, detailing the entire model presented, in order to encompass all the main levels of health care: primary, secondary and tertiary. For this, a review was carried out, aiming to analyze the characteristics of the disease, as well as to present its epidemiological data, associated with a detailing of the main points of the proposed Care Line. Among the results presented, there is a new method of integrating the networks of attention to meningococcemia, in order to guarantee a more effective care for patients with this disease, with the proposal of the new Line of Care. Finally, it is concluded that meningococcemia is a disease still present in a significant way in Brazilian territory. Therefore, the proposal of the Care Line is important because it fulfills the function of complementing the existing therapeutic measures.